Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1097/mcg.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Triglycerides in the Prognostic Assessment of Acute Pancreatitis

Abstract: Elevated serum TGs are related to a worse prognosis of AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 33 publications
10
69
1
Order By: Relevance
“…This include higher occurrence of renal failure, respiratory failure, shock, systemic inflammatory response syndrome and higher Acute Physiology and Chronic Health Evaluation (APACHE‐II) scores . Higher mortality rates are also reported for acute pancreatitis secondary to severe HTG , suggesting that HTG aggravates pancreatitis episodes. On the other hand, atherosclerotic cardiovascular disease (ASCVD) is considered to be a rare complication of FCS.…”
Section: Evidence Used In This Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This include higher occurrence of renal failure, respiratory failure, shock, systemic inflammatory response syndrome and higher Acute Physiology and Chronic Health Evaluation (APACHE‐II) scores . Higher mortality rates are also reported for acute pancreatitis secondary to severe HTG , suggesting that HTG aggravates pancreatitis episodes. On the other hand, atherosclerotic cardiovascular disease (ASCVD) is considered to be a rare complication of FCS.…”
Section: Evidence Used In This Reviewmentioning
confidence: 99%
“…Acute pancreatitis can be fatal with an overall mortality rate of ~ 6% , but can reach as high as 10–30% if severe complications are present . Although there is no correlation between the absolute maximal TG value and more severe pancreatitis episodes , a recent systematic review and meta‐analysis of observational studies found that HTG‐induced acute pancreatitis is associated with a worse prognosis compared to pancreatitis of other aetiology . This include higher occurrence of renal failure, respiratory failure, shock, systemic inflammatory response syndrome and higher Acute Physiology and Chronic Health Evaluation (APACHE‐II) scores .…”
Section: Evidence Used In This Reviewmentioning
confidence: 99%
“…Triglyceride, the main form of energy storage in the body, is stored in adipose tissue which is involved in a range of processes such as energy balance and fatty acids metabolism. Triglycerides are ester molecules derived from glycerol and three fatty acids 28 – 31 . Apoptosis is a process of programmed cell death that occurs in multicellular organisms 32 , 33 , which involve coordinated regulation of a broad range of genes.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective analysis of a large cohort with a triglyceride measurement of >500 mg/dl, the group with follow-up triglyceride values of <400 mg/dl were associated with a significantly lower rate of pancreatitis, indicating that the lower the triglyceride levels can be reduced the less likely will be the risk of pancreatitis (121). Furthermore in a meta-analysis of 15 studies that compared patients with HTG-induced pancreatitis and those with non-HTG-related pancreatitis, HTG-related pancreatitis was associated with an increased odds ratio for renal failure (OR 3.18), respiratory failure (OR 2.88), shock (OR 3.78) and mortality (OR 1.90), thus providing strong evidence for worse outcome when pancreatitis results from severe HTG (122).…”
Section: Complications Of the Chylomicronemia Syndromementioning
confidence: 99%